Temporal variation in the abundance and distribution of poeciliopsis fasciata in near-shore habitat of the high elevation lake, lago de achichilca, puebla, mexico (2012)
The distribution of organisms within a pond or lake can reflect the result of a variety of factors. We examined the distribution and abundance of the fish, Poecilioposis fasciata, in Lago de Achichilca, Puebla, Mexico, as well as how the distribution and abundance varied among months. Dissolved oxygen, temperature, and salinity varied among months. The abundance of P. fasciata peaked in December and February. For the months when fish were observed, their abundances were positively related to dissolved oxygen concentration and were generally not related to temperature. Our results make it clear that there is substantial seasonal variation in the abundances of P. fasciata and that within months, their distributions are likely driven more by dissolved oxygen than either temperature or salinity.